Interspecific Transfer of Streptomyces Giant Linear Plasmids in Sterile Amended Soil Microcosms - Ravel, Jacques (American Society for Microbiology, 2000)
The interspecific transfer of two giant linear plasmids was investigated in sterile soil microcosms. Plasmids pRJ3L (322 kb) and pRJ28 (330 kb), both encoding mercury resistance, were successfully transferred in amended soil microcosms from their streptomycete hosts, the isolates CHR3 and CHR28, respectively, to a plasmidless and mercury-sensitive strain, Streptomyces lividans TK24. Transconjugants of S. lividans TK24 were first observed after 2 to 3 days of incubation at 30°C, which corresponded to the time taken for the formation of mycelia in soil. Transfer frequencies were 4.8 × 10(−4) and 3.6 × 10(−5) CFU/donor genome for pRJ3L and pRJ28, respectively. Transconjugants were analyzed by pulsed-field gel electrophoresis for the presence of plasmids, and plasmid identity was confirmed by restriction digests. Total genomic DNA digests confirmed that transconjugants were S. lividans TK24. The mercury resistance genes were shown to be on the plasmid in the transconjugants by hybridization analysis and were still functional. This is the first demonstration of transfer of giant linear plasmids in sterile soil microcosms. Giant linear plasmids were detected in many Streptomyces spp. isolated from mercury-contaminated sediments from Boston Harbor (United States), Townsville Harbor (Australia), and the Sali River (Tucuman, Argentina). Mercury resistance genes were shown to be present on some of these plasmids. Our findings that giant linear plasmids can be transferred between Streptomyces spp. and are common in environmental Streptomyces isolates suggest that these plasmids are important in gene transfer between streptomycetes in the environment.